Conference report (including non-peer reviewed articles) from the 10th Nordic Conference on Reindeer Research, 13-15 March 1998, Kautokeino, Norway - Rolf Egil Haugerud (Editor) (Rangifer, 1999)
Nordic Council for Reindeer Research (NOR) arranged the 10th Nordic Reinndeer Research Conference in Kautokeino 13-15 March 1998. The main theme was Reindeer Husbandry in the Nordic countries.